PENGARUH DOSIS PAKAN BUATAN TERHADAP KELULUSHIDUPAN DAN PERTUMBUHAN LARVA IKAN NILEM (Osteochilus vittatus) - Ivana Yuniar Safitri; Nuhman Nuhman; Ninis Trisyani (Jurnal Perikanan Pantura (JPP), 2022)
Nilem fish is a native Indonesian commodity that has been cultivated for a long time by the community. Nilem fish has the potential to be developed into superior aquaculture products. Nilem fish cultivation is profitable in terms of economy, environmental sustainability, and aquaculture production. This study aims to determine the effect of giving different feed doses on survival and growth of nilem fish (Osteochilus vittatus) larvae. The research design used in this study was a completely randomized design (CRD) consisting of 5 treatments and 5 replications. Data analysis was carried out with normality test and homogeneity test then continued with ANOVA (Analysis of Variance) test and to find out the difference between one treatment and another, a further test was carried out, namely the Least Significant Difference Test (BNT). The results of this study showed that the best percentage of survival, absolute weight growth and daily growth rate of nilem fish (Osteochilus vittatus) larvae was obtained in treatment B (4% of feed dose from biomass) with successive values ​​of 97.72% ± 2.65, 0.22 grams ±2.65 and 8.23% ±6.76. This is because the amount of feed given can be utilized optimally by fish larvae so that it is not only for survival but also can support the growth process, and there is no turbidity (dissolved or suspended organic matter) in the live fish media which can result in inhibition of the growth of fish larvae.